2018
DOI: 10.1016/j.schres.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure predicts cognitive training-induced improvements in attention and executive functioning in schizophrenia

Abstract: We examined the relationship between white matter microstructure in schizophrenia using diffusion tensor imaging (DTI) and cognitive improvements induced by 70h (~16weeks) of cognitive training. We measured anatomical connectivity in 48 patients with schizophrenia (SZ) and 28 healthy control participants (HC) at baseline, and then examined the relationship between anatomical connectivity at baseline and training-induced cognitive gains in 30 SZ who performed diffusion imaging after completing 70h of training. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 65 publications
1
31
1
Order By: Relevance
“…WM fiber tracts are the neural architectures supporting high-speed interactions between different regions of the brain, and thus clinical and cognitive symptoms related to SCZ could be attributed to the alterations of WM pathways 38 . Previous studies have revealed the association between WM connections and cognitive performance in SCZ patients 39 43 . For example, executive and motor functioning deficits are linked to reduced WM integrity in the temporal and frontal connectivity in first-episode SCZ patients 32 .…”
Section: Introductionmentioning
confidence: 99%
“…WM fiber tracts are the neural architectures supporting high-speed interactions between different regions of the brain, and thus clinical and cognitive symptoms related to SCZ could be attributed to the alterations of WM pathways 38 . Previous studies have revealed the association between WM connections and cognitive performance in SCZ patients 39 43 . For example, executive and motor functioning deficits are linked to reduced WM integrity in the temporal and frontal connectivity in first-episode SCZ patients 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The radio-crown refers to the radial white matter bers from the inner capsule to the cerebral cortex, and the spatial arrangement of various projection bers with different functions is currently not completely clear [11] . Many studies have found varying degrees of damage to the right or bilateral radio-crown in patients with schizophrenia [12][13] . In this paper, the FA values in the right anterior radio-coronal region in patients with DS were lower compared with NDS patients, suggesting that the integrity of white matter bers in the radio-crown is more seriously damaged.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown at a group level, that the intact structure of thalamicprefrontal regions was also an important determinant of successful responsivity to cognitive training interventions in SCZ (14). Additionally, Ramsay et al showed that cognitive training was associated with increased thalamic-prefrontal activity and connectivity such that improved recruitment after cognitive training became correlated with overall improved cognitive functions (33).…”
Section: Discussionmentioning
confidence: 98%
“…Although these findings are promising at the group level, it is clear that there is a large amount of inter-individual variability in neural system and functional response to various forms of CT. Previous group-based studies have shown that baseline structural anatomical integrity (12)(13)(14) is associated with greater responsiveness to CT, suggesting that certain individual neurobiological characteristics might determine who will benefit the most from this intervention, but individual-level predictions have not yet been demonstrated. In particular, prior research indicates that patients with schizophrenia (SCZ) show most prominent deficits in auditory processing, that contributed to higher-level cognitive impairments and poor functioning (15)(16)(17) Promisingly, we have also found that the most prominent gains in auditory/verbal functions were induced after auditory-based CT (ABCT) interventions (18)(19)(20)(21)(22) This work prompted us to investigate multivariate pattern analyses (MVPA) to identify baseline patterns in grey matter (GM) volume in patients with schizophrenia (SCZ) that predicted improved functioning after an auditory-based CT (ABCT) intervention, operating at the single subject level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation